Foam stability of temperature-resistant hydrophobic silica particles in porous media - Qiao, Sanyuan; Yu, Haibin; Wang, Yongan; Zhan, Lifeng; Liu, Qingwang; Fan, Zhenzhong; Sun, Ao (Frontiers in Chemistry, 2022)
The world is rich in heavy oil resources, however, the recovery difficulty and cost are both higher than that of conventional crude oil. To date, the most common method of recovering heavy oil is steam flooding. However, once the steam breaks through the geological formation, gas channeling readily occurs, which leads to a rapid decrease of the steam drive efficiency. To improve the swept volume of steam in the geological formation, a series of hydrophobic silica particles for stabilizing foam was synthesized. This kind of particles used hydrophilic nano silica particles as reactant. Hydrophobic groups with cationic long carbon chains were grafted onto the surface of hydrophilic silica particles by synthetic silane quaternary ammonium salt. When the quantity of silane quaternary ammonium salt used in the modification reaction is different, the product had various degrees of wettability. The hydrophobic particles with the contact angle closest to 90 ° had the best foam stabilization effect on the betaine zwitterionic surfactant LAB. For LAB solution with mass fraction of 0.3%, the half-life of foam was extended into 160% when the mass fraction of particles was 0.5%. The higher the gas-liquid ratio, the better the plugging effect of foam agent with hydrophobic particles presented in porous media. The adsorption test of hydrophobic particles indicated that hydrophobic particles improved the stability of foam liquid membrane by improving the adsorption capacity of surfactant molecules. The thermal stability of hydrophobic silica particles exceeded 200 ℃, and the good foam stability made it a potential additive for foam oil displacement in high-temperature geological formation.